Influence of prominent immunomodulatory cytokines TNF‐α308 G>A (rs1800629) and TGFβ1 G>C (rs1800471) sequence variations as an important contributing factor in etiopathogenesis of recurrent miscarriages in Kashmiri women (North India). Issue 5 (23rd February 2021) - Manzoor, Usma; Pandith, Arshad A.; Amin, Ina; Wani, Saima; Sanadhya, Dheera; Ahmad, Abida; Qasim, Iqbal; Rashid, Masarat; Anwar, Iqra; Koul, Aabid
Abstract: Aim: We aimed to evaluate the genetic variation of tumor necrosis factor‐α (TNF‐α) 308 G>A (rs1800629) and transforming growth factor (TGF) β1G>C (rs1800471) to confer risk in patients with recurrent miscarriage in highly consanguineous population of Kashmir (North India). Methods: A total of 200 women who experienced two or more recurrent miscarriages (along with 100 spouses, 60 products of conception, and 240 healthy controls) with two or more full‐term pregnancies were recruited from the same geographical region and evaluated by polymerase chain reaction‐restriction fragment length polymorphism method. Results: TNF‐α 308 G>A variant genotype (AA) was significantly associated with recurrent miscarriage cases (2.5% vs. 0.4% controls, respectively; p < 0.05) and its per copy allele A also presented more in cases (32% vs. 24% in controls; p < 0.05) that showed a risk of 1.5‐fold for cases ( p < 0.05). The difference of variant genotype GA was observed to be significant among recurrent miscarriage cases and product of conception: 60.5% vs. 83%, respectively ( p < 0.05) wherein variant TNF‐α GA genotype conferred 3‐fold risk ( p < 0.05). On the other hand, TGF β1 G>C showed no association with recurrent miscarriage cases in our population. Conclusion: The study found both TNF‐α 308 G>A variants are significantly associated with an increased susceptibility for recurrent miscarriages to cause pregnancy losses but on the other hand TGF β1 does not seem to impact the outcome of pregnancy in our population.